HUMAN RESOURCE MANAGEMENT IN ENHANCING EMPLOYEE WORK COMMITMENT AT THE FACULTY OF HEALTH SCIENCES MUHAMMADIYAH UNIVERSITY OF TANGERANG - Fauzan Hakim; Hengki Nurhuda (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the implementation of human resource management in strengthening employee work commitment at the Faculty of Health Sciences, Universitas Muhammadiyah Tangerang. A qualitative descriptive research design was employed to obtain an in-depth understanding of the phenomenon. Primary data were collected through direct observation and semi-structured interviews with faculty leadership, administrative staff, and department heads, while secondary data were derived from scholarly literature and institutional documents. The findings reveal that effective human resource management practices, including transparent recruitment, competency-based training, fair performance appraisal, and motivational leadership, contribute significantly to enhancing employees' work commitment and work enthusiasm. These elements foster a positive organizational culture that encourages employee loyalty, discipline, and proactive engagement. When employees perceive genuine concern for their professional development and well-being, their sense of belonging and dedication increases, leading to improved performance and reduced turnover intentions. Consistent communication between management and staff is also key to sustaining motivation. In conclusion, strategic human resource management plays a pivotal role in strengthening employee commitment, supporting organizational performance and long-term sustainability.